PENINGKATAN KOMPETENSI PROFESIONAL GURU: PELATIHAN MENGEMBANGKAN BUKU AJAR AKUNTANSI BAGI GURU MGMP AKUNTANSI KOTA TANGERANG - Indriawati, Fitri; Yessie, Afly; Mahroji, Mahroji (Transpublika Publisher, 2024)
This training aims to enhance the core competencies of MGMP Accounting teachers in Tangerang City by improving their mastery of subject matter, structure, concepts, and scientific mindset that support the subjects they teach, and by creatively developing learning materials. The research used the direct experimental method, collecting data through observation, interviews, and documentation. The results showed that the training program successfully increased teachers' competence in mastering the material and developing teaching materials, demonstrated by the preparation of teaching material books. Additionally, qualitative results indicated that participants felt delighted and enthusiastic about the training program, recognizing the benefits and satisfaction with the interactive delivery method and relevant material. Although there were time constraints in preparing the book chapters, the training has proven to increase teachers' professional competence in developing teaching materials and improving the quality of accounting education in Tangerang City.